Breakfast with Her Excellency and Other Notes of a Zoo Director - Miroslav, Bobek (Universum, 2025)
The new book by Miroslav Bobek, the Prague Zoo Director, full of gripping texts and interesting photographs, answers even the most inquiring questions - what does the transport of gorilla female entail? How did Prague Zoo look in its early days and how are new houses built? And do you know why the famous football player Karel Poborský played in a football match in Cameroon? Have a look behind the scenes (and not only) of a zoological garden!
Keywords: Memoáry, osobnosti a osudy